2015
DOI: 10.5194/asr-12-179-2015
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of European droughts under a moderate emission scenario

Abstract: Abstract. Meteorological drought is generally defined as a prolonged deficiency of precipitation and is considered one of the most relevant natural hazards as the related impacts can involve many different sectors. In this study, we investigated the spatial patterns of European droughts for the periods 1981-2010, 2041-2070, and 2071-2100, focusing on the projections under a moderate emissions scenario. To do that, we used the outputs of the KNMI-RACMO2 model, which belongs to the A1B family and whose spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 48 publications
0
35
0
1
Order By: Relevance
“…Besides undisturbed plots that received ambient precipitation, we installed a replicated set of rainout-shelters that were identical to our original rainoutshelters, but allowed all natural precipitation to reach the area under the rainout-shelter (V-bands were turned over to become -bands). The partial reduction of rainfall simulated by our rainout-shelters reflects predictions of future precipitation changes during the crop growing season in Central Europe (Russo et al, 2013;Spinoni et al, 2015;EEA, 2017). Our rainoutshelters are suitable for studies in a wide range of ecosystems, including agricultural systems, as they are both stable enough to endure extreme weather events in open land and are removable to allow for management activities.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Besides undisturbed plots that received ambient precipitation, we installed a replicated set of rainout-shelters that were identical to our original rainoutshelters, but allowed all natural precipitation to reach the area under the rainout-shelter (V-bands were turned over to become -bands). The partial reduction of rainfall simulated by our rainout-shelters reflects predictions of future precipitation changes during the crop growing season in Central Europe (Russo et al, 2013;Spinoni et al, 2015;EEA, 2017). Our rainoutshelters are suitable for studies in a wide range of ecosystems, including agricultural systems, as they are both stable enough to endure extreme weather events in open land and are removable to allow for management activities.…”
Section: Introductionmentioning
confidence: 57%
“…Climate change models predict a future increase in temperature and altered precipitation regimes for Central Europe (Russo et al, 2013;Spinoni et al, 2015;EEA, 2017) as well as on a global scale (IPCC, 2014). For Switzerland, average annual precipitation is predicted to decrease by 21-28% by the end of the century, accompanied by more frequent drought events in summer (CH2011, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The same approach was used in Spinoni et al . (, , , ) and is based on the definitions provided by McKee et al . (, ).…”
Section: Methodsmentioning
confidence: 81%
“…We highlight that the same approach was chosen in the previous studies of Spinoni et al . (, ), consequently we decided to adapt it to this study in order to give continuity.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, previous studies e.g. Sheffield and Wood (2008), Dai (2011), Orlowsky andSeneviratne (2013) and Spinoni et al (2015a) have shown that increases in drought impacts during the recent past were not driven by decreased precipitation only, but also by increased evapotranspiration, highlighting that trends in precipitation emerge slowly and their effects on extreme climate events, such as drought, only establish in the longer-term. …”
Section: Projections For the Period 2021-2050mentioning
confidence: 93%